2018
DOI: 10.18388/abp.2017_2341
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 mediates phorbol ester (PMA)-induced expression of membrane-bound guanylyl cyclase GC-A in human monocytic cells*

Abstract: Cyclic guanosine monophosphate (cGMP) is synthesized by two types of enzymes: particulate (membrane-bound) guanylyl cyclases (pGCs) and soluble (cytosolic) guanylyl cyclases (sGCs). sGCs are primarily activated by binding of nitric oxide to their prosthetic heme group while pGCs are activated by binding of peptide ligands to their extracellular domains. One of them, pGC type A (GC-A) is activated by atrial and brain natriuretic peptides (ANP and BNP, respectively). Human monocytes isolated from peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…The TMBIM6 upregulation in the PMA treatment condition could be mediated also through Sp1. Sp1 was previously shown to mediate the PMA-induced expression of membrane-bound GC-A in human monocytic THP-1 cells and the expression of the TMBIM6 gene in airway epithelial cells [57,58]. In this study, NF-κB and AP2 sites were found in the core promoter region of TMBIM6; therefore, the PMA mediated-enhancement of TMBIM6 expression might also be mediated through those factors [56].…”
Section: Discussionmentioning
confidence: 57%
“…The TMBIM6 upregulation in the PMA treatment condition could be mediated also through Sp1. Sp1 was previously shown to mediate the PMA-induced expression of membrane-bound GC-A in human monocytic THP-1 cells and the expression of the TMBIM6 gene in airway epithelial cells [57,58]. In this study, NF-κB and AP2 sites were found in the core promoter region of TMBIM6; therefore, the PMA mediated-enhancement of TMBIM6 expression might also be mediated through those factors [56].…”
Section: Discussionmentioning
confidence: 57%